Effect of Intravenous Morphine Injection on Neurological Examination of Dogs With Thoracolumbar Intervertebral Disk Extrusion - Fouhety, Aurore; Bruwier, Aurelie; Bassanino, Jean; Gabriel, Alexandra; Boursier, Jean-François; Bedu, Anne-Sophie; Leperlier, Dimitri (Frontiers in Veterinary Science, 2020)
Objectives: We aimed to determine the effect of intravenous morphine injection on the modified Frankel scores of dogs with thoracolumbar intervertebral disk extrusion (IVDE). Methods: This was a prospective, blinded, randomized, and placebo-controlled study. We included dogs with a presumptive diagnosis of thoracolumbar IVDE that did not undergo analgesic, anti-inflammatory or sedative treatment within the last 12 hours. A neurological examination was performed and the deficits were graded using the modified Frankel score (MFS). Subsequently, each dog was randomly allocated to receive an intravenous injection of either morphine or placebo. After 30 minutes, the dogs were re-evaluated by the same veterinary officer who was blinded to the contents of the injections. Dogs were included in the study if IVDE was ultimately confirmed by surgery within one week of initial presentation. Results: Among the 79 dogs initially enrolled, 62 dogs met the inclusion criteria. Among them, thirty-two dogs received intravenous morphine injections and there was no difference between the pre- and post-injection modified Frankel scores. Thirty dogs received an intravenous placebo injection. One dog had a worsening of the MFS by one grade in the post-injection examination. Clinical Significance: In dogs with thoracolumbar intervertebral disk extrusion, an intravenous injection of morphine does not affect the modified Frankel score after 30 minutes compared with the pre-injection value. These findings support the use of an analgesic morphine dose if the neurological examination can be performed 30 minutes or later after the injection.